2003
DOI: 10.1515/bc.2003.143
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleosome-Free dG-dC-Rich Sequence Element Promotes Constitutive Transcription of the Essential Yeast RIO1 Gene

Abstract: RIO1 is an essential gene that encodes a protein serine kinase and is transcribed constitutively at a very low level. Transcriptional activation of RIO1 dispenses with a canonical TATA box as well as with classical transactivators or specific DNA-binding factors. Instead, a dG-dC-rich sequence element, that is located 40 to 48 bp upstream the single site of mRNA initiation, is essential and presumably constitutes the basal promoter. In addition, we demonstrate here that this promoter element comprises a nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It is possible that the tissue expression pattern of the RIOKs is wider than our analysis showed when the expression specific levels are very low. Indeed, both Rio1P and Rio2P are reported to be expressed at very low levels in yeast [ 6 , 33 ]. Therefore, it is possible that riok-1 and- 2 are expressed widely, but at very low levels in C. elegans and may function in rRNA processing, as is the case in other species.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the tissue expression pattern of the RIOKs is wider than our analysis showed when the expression specific levels are very low. Indeed, both Rio1P and Rio2P are reported to be expressed at very low levels in yeast [ 6 , 33 ]. Therefore, it is possible that riok-1 and- 2 are expressed widely, but at very low levels in C. elegans and may function in rRNA processing, as is the case in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence profile analysis of bacterial H-NOX domains showed that they are found in predicted operons encoding genes for two component systems and diguanylate cyclases or phosphodiesterases. Furthermore, fused PAS/coiled-coil domain genes are frequently in close proximity to H-NOX genes in bacterial genomes (30). In sGC, multiple protein domains must transfer signals to each other via direct and allosteric signaling mechanism involving many regulatory interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, we believe that phosphorylation of Rio1p by CK2 has at least two biologically relevant consequences: (a) it increases Rio1 kinase activity and, conceivably, also controls interaction with other proteins (presumably during the G 1 phase); and (b) it provides a signal for commitment for degradation of Rio1p before entrance of the S phase. We have shown for the first time that the cellular concentration and activity of constitutively expressed Rio1p [15,16] are likely regulated through phosphorylation by CK2.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential in yeast and is only distantly related to previously characterized protein kinases. The RIO1 gene is transcribed constitutively at an extremely low level [15,16], and Rio1p is a very low abundant protein [12]. Yeast has only one such gene, whereas at least two orthologues of Rio1p are present in higher eukaryotes.…”
mentioning
confidence: 99%